2014
DOI: 10.1039/c3nr06539a
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide conversion into hydrocarbon fuels on defective graphene-supported Cu nanoparticles from first principles

Abstract: Density functional theory studies demonstrate that defective graphene-supported Cu nanoparticles can modify the structural and electronic properties of copper for enhancing electrochemical reduction of carbon dioxide (CO2) into hydrocarbon fuels (CH4, CO, and HCOOH). We not only provide improved understanding of CO2 conversion mechanisms on both Cu and the Cu nanoparticle system, but also explain a key factor for enhanced CO2 conversion. A promising catalytic material for CO2 conversion into hydrocarbon fuels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(123 citation statements)
references
References 40 publications
4
119
0
Order By: Relevance
“…Lim et al predicted a strong interaction between Cu nanoparticles and carbon, and we expect that to extend to CNS as well. [12] We expect that the strong interaction provides an environment in which a mechanism involving reactive sites on both the Cu surface and on the N-doped CNS may dominate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lim et al predicted a strong interaction between Cu nanoparticles and carbon, and we expect that to extend to CNS as well. [12] We expect that the strong interaction provides an environment in which a mechanism involving reactive sites on both the Cu surface and on the N-doped CNS may dominate.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Polycrystalline Cu foil produces a mixture of compounds in CO 2 -saturated aqueous solutions that are dominated either by H 2 at low overpotential, or by CO and HCOO À at high overpotential, or by hydrocarbons and multi-carbon oxygenates at the most extreme potentials. [9,11] Theoretical studies predict that graphene-supported Cu nanoparticles would enhance catalytic activity due to the strong Cu -graphene interaction via defect sites, [12] which would stabilize the intermediates from CO 2 reduction and improve selectivity towards hydrocarbon products as methane and methanol at lowered overpotential. Early studies revealed that the electrode surface was dominated by adsorbed CO during the CO 2 reduction and that CO acted as intermediate in the production of hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [30] Copyright 2014, Royal Society of Chemistry. c) The adsorption and the free energy profile of CO 2 ERR on the penta-twinned Cu nanowire.…”
Section: Inducing Adsorption Sites With Oxophilicitymentioning
confidence: 98%
“…Lim et al used DFT to study Cu nanoparticles (Cu 55 ; diameter of approximately 0.9 nm) on a defective graphene system. [106] The Cu 55 exhibited strong adsorption on the graphene with adsorption energy of -4.26 eV. This was attributed to the dangling bonds of carbon atoms adjacent to the 5-8-5 vacancy site interacting with the copper atoms and is thought to be key in preventing sintering of the nanoparticles.…”
Section: Nanostructured Carbon Supportsmentioning
confidence: 99%